Dehumanization of Bullying Against Persons with Disabilities at UIN Sunan Kalijaga: Hadist Appoach - Amelza Putra, Feby (JPI (Jurnal Pendidikan Inklusi), 2024)
The Learning Process at UIN Sunan Kalijaga for students with disabilities is hindered by communication during the learning process in class. The purpose of this study is to find out the meaning of the phenomenon of bullying that occurs in disabilities from the perspective of hadith. The method used is descriptive-analytical. The long-term implications if this continues to happen will cause a decrease in the physical and mental well-being of the victim, worse it will harm all aspects of psychological life and will last a lifetime. That way the research to be carried out because there are still many who turn a blind eye to cases of bullying, especially in people with disabilities.